Intelligent Bicycle Safety and Tracking System: A GPS and GSM-Based Approach - Ibrahim A. Ameen (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Bicycles are affordable and healthy, cause zero harm to the environment, require little space on roads and parks, and are not noisy transportation means. However, cyclists face challenges on roads, which may lead to injuries and deaths. For instance, cyclists visibility, speed management, ability to communicate with other road users, backward accidents, and ability to be located in urgent cases. This paper presents performance, tracking, and safety systems from hardware and software point of view. As a result, cyclists monitor their speed to manage; their locations are tracked, and their cycling paths are traced. Also, a rear red light and turn signal LEDs are activated without any physical action from the rider to communicate with other drivers. Moreover, a microwave radar sensor with a range of seven meters is employed to protect the cyclist from backward-approaching vehicles. Finally, three Arduino UNO boards with GPS, GSM modules, MPU-6050, and RCWL-0516 sensors are mounted on a conventional bicycle to provide safer trips.